Pelatihan Penguatan Kemampuan Akademik dan Berpikir Logis bagi Siswa SMK dalam Menghadapi Tes Kemampuan Akademik (TKA) - Jayanti Munthahana (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to improve the academic competence and logical thinking skills of vocational high school students in preparing for the Academic Competency Test (TKA). The program was conducted at SMK 1 PGRI Gresik using a participatory and collaborative approach, involving lecturers and supervising teachers. The methods employed included interactive workshops, concept-based instruction, problem-based learning, practice exercises, and reflective mentoring. Evaluation instruments consisted of questionnaires, which were analyzed using descriptive quantitative methods, gain score calculations, and a paired-sample t-test. The results showed that the maximum and minimum scores on the tryout test were 60 and 5, respectively, while the maximum and minimum post-test scores were 79 and 16. The average tryout score was 34.32 and increased to 47.11 in the post-test. Gain score analysis produced an N-Gain value of 0.216, which falls into the low category. However, the paired-sample t-test showed a significance value of 2.0023E-07 (p < 0.05), indicating that the improvement was statistically significant. In addition, students demonstrated positive perceptions regarding mastery of academic materials, understanding of problem-solving strategies, frequency and independence in study practice, and psychosocial readiness to face the TKA, with an average score of 2.64 categorized as agree.